1986
DOI: 10.1002/etc.5620050409
|View full text |Cite
|
Sign up to set email alerts
|

Relative sensitivity of three daphnid species to selected organic and inorganic chemicals

Abstract: Static acute and renewal chronic tests were conducted with Daphnia magna, Daphnia pulex and Ceriodaphnia reticulata to determine their relative sensitivities to selected organic and inorganic chemicals: 2-chloroethanol, 2,4-pentanedione, pentachlorophenol, hexachloroethane, 2,2,2-trichloroethanol, 2-methyl-l-propanol, 2-methyl-2,4-pentadiol, Endrin@, silver, lead, chromium, cadmium, copper, arsenic and mercury. The three species tested yielded comparable acute EC50 values for most chemicals tested. The acute E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 14 publications
4
19
3
1
Order By: Relevance
“…The LC50 values, 3.2% and 13.4%, probably do not differ significantly. These findings are in contrast to that of Elnabarawy, et al (14), who found Daphnia magna, Daphnia pulex and Ceriodaphnia reticulata equally sensitive to various organic, inorganic and pesticide chemicals in both acute and chronic tests. While cladocera may be equally sensitive to pure chemicals, they may not respond in the same way to the possible additive, synergistic or antagonistic toxicity dynamics present in municipal effluents.…”
Section: Acute Toxicity Testscontrasting
confidence: 85%
“…The LC50 values, 3.2% and 13.4%, probably do not differ significantly. These findings are in contrast to that of Elnabarawy, et al (14), who found Daphnia magna, Daphnia pulex and Ceriodaphnia reticulata equally sensitive to various organic, inorganic and pesticide chemicals in both acute and chronic tests. While cladocera may be equally sensitive to pure chemicals, they may not respond in the same way to the possible additive, synergistic or antagonistic toxicity dynamics present in municipal effluents.…”
Section: Acute Toxicity Testscontrasting
confidence: 85%
“…[15] Our results in C. dubia with Cr(VI) are similar to those reported by Elnabarawy et al (0.195 mg L −1 ), [36] and although Cowgill and Milazzo [30] report a 5-times higher value (1.2 mg L −1 ), the difference could be due to the higher hardness of the dilution water used by them.…”
Section: Comparative Sensitivity Among Speciessupporting
confidence: 91%
“…Much lower lethality threshold for both Cr(V1) and Cr(II1) have been reported, however. Elnabarawy et al (1986) found a 20% death rate for adult Daphnia pulex exposed to 1.5 kg Cr(VI)/L. The lowest reported median lethal concentration (LC50) for Daphnia magna was 6 kg/L for Cr(II1) (Janus and Krajnc 1990).…”
Section: Aquatic Biotamentioning
confidence: 97%